Antioxidant Activity of Gel Formulations Containing Various Plant Leaf Extracts: A Review - Valentin, Diva; Ratnasari, Devi; Az-zahraa, Ailla; Cahyani, Theresia Natalie; Shella, Tasya Permata; Adzkia, Muhammad Adit (Jurnal Pijar Mipa, 2025)
Antioxidants protect the skin from the adverse effects of free radicals, which can potentially trigger premature aging and even skin cancer. Free radicals, with unpaired electrons, are highly reactive and can damage cellular structures. However, the high risk of side effects from synthetic antioxidants, such as skin cancer, has increased interest in natural sources. In cosmetic formulations, gel preparations are highly favored because they can optimally and stably deliver active ingredients to the skin. This study employed a literature review method by examining and collecting articles from relevant scientific journals published over the past 10 years (2014–2024), with 13 articles as primary references. The analysis found that several extracts, such as leilem leaf, pandan, and green tea, exhibited strong antioxidant potential, as indicated by low IC50 values, making them ideal as active ingredients in gel formulations. In addition to the type of plant leaves, the effectiveness of these antioxidants is influenced by the extract concentration used, solvent selection during extraction, and the processing techniques employed in formulation.